DISCOVERY LEARNING IN TEACHING THE EXPRESSION OF GIVING OPINION TO THE ELEVENTH GRADERS OF SMAN 1 KRIAN (RETAIN, 2016)
DISCOVERY LEARNING IN TEACHING THE EXPRESSION OF GIVING OPINION TO THE ELEVENTH GRADERS OF SMAN 1 KRIAN Elsa Alvarisi English Education Department, Language and Art Faculty, Surabaya State University. elsaalvarisi@mhs.unesa.ac.id Ririn Pusparini English Education Department, Language and Art Faculty, Surabaya State University. rrn.puspa@gmail.com Abstrak Penelitian ini bertujuan untuk mendeskripsikan penerapan model pembelajaran berbasis penemuan untuk mengajar ungkapan memberi pendapat pada siswa kelas sebelas SMAN I Krian, dan untuk mendeskripsikan hasil berbicara siswa selama penerapan model pembelajaran berbasis penemuan, dan mengetahui respon siswa terhadap penerapan model pembelajaran berbasis penemuan. Dalam penelitian ini, peneliti melaksanakan observasi yang berhubungan dengan manfaat model pembelajaran berbasis penemuan dalam pengajaran ungkapan memberi pendapat. Selain itu, peneliti melaksanakan penelitian kualitatif sebagai desain penelitian. Implementasi model pembelajaran berbasis penemuan dengan sukses diterapkan sebagai model untuk mengajar ungkapan memberi pendapat pada kelas XI SMAN I Krian. Disamping itu, siswa tertarik dan terlibat dalam proses belajardengan antusias. Mereka juga dapat meningkatkan kemampuannya untuk berbicara selama implementasi model pembelajaran berbasis penemuan. Kata Kunci: Berbicara, Model Pembelajaran Berbasis Penemuan, Memberi Pendapat. Abstract This study is conducted to describe the implementation of Discovery Learning in teaching the expression of giving opinion to the eleventh graders of SMAN 1 Krian, the students’ speaking competence during the implementation of discovery learning in teaching the expression of giving opinion of SMAN 1 Krian and the students’ responses towards the use of discovery learning in teaching the expression of giving opinion of SMAN 1 Krian. The researcher was conducted an observation which related to the use of Discovery learning to teach speaking. Moreover, the researcher conducted descriptive qualitative research as a research design. Discovery learning was successfully used as a model to teach the expression of giving opinion to the eleventh graders of SMAN I Krian. In addition, the students were interested and involved in the learning process enthusiastically. They also could enhance their ability to speak during the implementation of Discovery Learning. Keywords: Speaking Skill, Discovery Learning, Giving Opinion